Enabling reusability of plant phenomic datasets with MIAPPE 1.1 - Papoutsoglou, Evangelia A.; Faria, Daniel; Arend, Daniel; Arnaud, Elizabeth; Athanasiadis, Ioannis N.; Chaves, Inês; Coppens, Frederik; Cornut, Guillaume; Costa, Bruno V.; Ćwiek-Kupczyńska, Hanna; Droesbeke, Bert; Finkers, Richard; et al. (Wiley, 2020)
Enabling data reuse and knowledge discovery is increasingly critical in modern science, andrequires an effort towards standardising data publication practices. This is particularly chal-lenging in the plant phenotyping domain, due to its complexity and heterogeneity. We have produced the MIAPPE 1.1 release, which enhances the existing MIAPPE standardin coverage, to support perennial plants, in structure, through an explicit data model, and inclarity, through definitions and examples. We evaluated MIAPPE 1.1 by using it to express several heterogeneous phenotyping exper-iments in a range of different formats, to demonstrate its applicability and the interoperabilitybetween the various implementations. Furthermore, the extended coverage is demonstratedby the fact that one of the datasets could not have been described under MIAPPE 1.0. MIAPPE 1.1 marks a major step towards enabling plant phenotyping data reusability,thanks to its extended coverage, and especially the formalisation of its data model, whichfacilitates its implementation in different formats. Community feedback has been critical tothis development, and will be a key part of ensuring adoption of the standards.